The making of neoliberal India : nationalism, gender, and the paradoxes of globalization - Oza, Rupal (Women Unlimited, 2006)
This is an ambitious study of gender and politics in India, and will be of interest to scholars of women's studies, globalization, postcolonialism, geography, media studies, and cultural studies, as well as India more generally.